Google Street View: navigating the operative image. - Hoelzl, Ingrid; Marie, Rémi (Visual Studies, 2014)
Via a close navigation of a Google Street View (GSV) scene in Oslo, this article investigates the role the photographic image plays in what has come to be known as ‘locative media’ – an entire range of image software that runs on mobile devices using GPS signals to locate the user, and that emerged after the United States government decided to end the intentional degradation of the public GPS signal in 2001, fostering the development of navigable photo-maps such as GSV, photo-synths and other location-based image applications such as Augmented Reality. The authors first address the temporal discontinuities and gaps of the GSV database, which the user navigates as a spatially continuous image. Second, they show that the city is experienced as one and the same data space, simultaneously traversed both on-site and on-screen. Third, they critically interrogate the navigability of the GSV image afforded by real-time data processing based on mutual data exchanges between user location, hardware, software, network and database. They argue that the GSV image is what Harun Farocki, in an article on cybernetic warfare, has called an ‘operative image’, an image that no longer represents an object but is part of an operation. In fact, the users’ trajectories feeding back into the database initiate a reverse operativity, which proves to be the more problematic side of ubiquitous locative media applications such as GSV.